Is Surgery-first Still a Reasonable Option in the Era of Neoadjuvant Chemotherapy for Resectable Pancreatic Cancer?. (April 2020) - Saharia, Ashish; Potter, Lucy M.; Baio, Flavio; Elaileh, Ahmed; Mobley, Constance; Ghobrial, Rafik M.; Abdelrahim, Maen; Heyne, Kirk
Abstract : The incidence of pancreatic ductal adenocarcinoma has risen rapidly. By 2030, it is likely to be the second most prevalent cause of death by cancer, following cancer of the lung. Unfortunately, most patients present with advanced disease. In fact, only 20% of patients are candidates for surgery. More research is needed to find dependable treatment options for this disease. Although we wait for more effective treatments to be developed, we continue using chemotherapy, radiation, and surgery—all with less than optimal outcomes. There is a debate about using chemotherapy in the neoadjuvant setting and counter-debate about better outcomes in the adjuvant settings. In the neoadjuvant setting, not everyone is able to make it to surgery; conversely, in the adjuvant setting, not everyone is able to make it to chemotherapy. Drop-out data after surgery are widely available, but similar drop-out rates after neoadjuvant treatment are not widely published. Here, we will analyze the literature to better understand the treatment strategies and outcomes of pancreatic ductal adenocarcinoma. We argue in favor of an upfront surgery and adjuvant therapy strategy for better outcomes and patient quality of life.